PENGARUH GAYA HIDUP, CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN BARBERSHOP DEN BAGOES TANGGUL JEMBER - Yurico, Bagus; Fatimah, Feti; Rahayu, Jekti (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Haircut is a necessity for people every month, men are no exception. To fulfill these needs, haircut services have sprung up that offer haircuts to special men's hair care. The form of business for men's haircut services is a barbershop. This study aims to analyze and test the role of lifestyle, brand image and service quality on customer satisfaction at Den Bagoes Barbershop Tanggul. The type of data in this study uses quantitative data in the form of online questionnaires. The sample population used in this study was 140 respondents with a non-probability sampling technique. Data collection techniques include primary data and secondary data. Data collection techniques using a Likert scale. The analytical tool in this study uses multiple linear regression analysis supported by instrument testing, classical assumption testing and hypothesis testing. The results of this study prove that lifestyle has a significant effect on customer satisfaction. Brand image has a significant effect on customer satisfaction. Service quality has a significant effect on customer satisfaction. The coefficient of determination in the variable model is 0.631. From these values ​​it can be concluded that lifestyle, brand image and service quality have a contribution of 63.1% to the formation of variations in customer satisfaction values, while the remaining 36.9% is explained by other factors outside the model.